Evaluation of stingless bee honey quality (Tetragonula laeviceps) based on their physicochemical from different origins - Agussalim Agussalim; Ardo Sabir; Muhamad Sahlan; Ali Agus (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Agussalim, Sabir A, Sahlan M, Agus A. 2023. Evaluation of stingless bee honey quality (Tetragonula laeviceps) based on their physicochemical from different origins. Biodiversitas 24: 2134-2142. Honey is a natural food mainly composed of sugars and other components such as enzymes, amino acids, organic acids, carotenoids, vitamins, minerals, and aromatic substances. This study aimed to determine the quality of stingless bee honey (Tetragonula laeviceps) based on their physicochemical from different origins of Lombok, Magelang, and Purworejo (Indonesia). The honey was physicochemically analyzed on its moisture, fat, protein (by proximate analysis), energy (bomb calory meter), flavonoid, phenolic, and DPPH antioxidant (spectrophotometer Uv-Vis), organic and amino acids (high-performance liquid chromatography). Honey from Lombok was lower in moisture content (p<0.01) and higher in protein, energy, citric acid, propionic acid, phenolic, flavonoid, DPPH antioxidant, amino acids (aspartic acid, glutamic acid, asparagine, glycine, and threonine) than honey from Magelang and Purworejo (p<0.01). Also, the citric acid of honey from Lombok and Magelang was similar. It was higher than citric acid honey from Purworejo (p<0.01). The lactic acid of honey from Lombok and Purworejo was similar. Both were higher than the lactic acid of honey from Magelang (p<0.05), but not on fat, butyric acid, and other amino acids. Thus, T. laeviceps honey from Lombok has a better quality based on physicochemical than honey Magelang and Purworejo. Honey from T. laevicepsis rich in phenolic and flavonoids to support the higher antioxidant.